Tadalafil Enhances the Therapeutic Efficacy of Mesenchymal Stem Cells-Derived Exosomes in Pulmonary Hypertension by Upregulating miR-29a-3p - Liu Y; He C; Zhong Q; Shi X; Li H; Fu G; Guo L; Zhao C; Tian L; Li X; Jiao X; Shan L (International Journal of Nanomedicine)
Yi Liu,1,2 Changqing He,1 Quanhai Zhong,3 Xianbao Shi,4 Hongyan Li,1 Gaoge Fu,1 Lixuan Guo,1 Churong Zhao,1 Lei Tian,1 Xin Li,1 Xue Jiao,1 Lina Shan1 1Department of Respiratory Disease, The First Affiliated Hospital, Jinzhou Medical University, Jinzhou, 121000, People’s Republic of China; 2Department of Critical Care Medicine, Panzhihua Central Hospital, Panzhihua, 61700, People’s Republic of China; 3Clinical Drug Laboratory, People’s Hospital of Yichun City, Yichun, Jiangxi, 336000, People’s Republic of China; 4Department of Pharmacy, The First Affiliated Hospital of Jinzhou Medical University, Jinzhou, People’s Republic of ChinaCorrespondence: Lina Shan, Email shanlina321@163.comIntroduction: Pulmonary hypertension (PH) is a progressive and life-threatening condition. Recent research has demonstrated that exosomes derived from mesenchymal stem cells (MSC) exhibit significant therapeutic potential in the treatment of PH. The composition of these exosomes is often substantially influenced by the characteristics of their parental cells. This study aimed to identify an intervention strategy to enhance the efficacy of mesenchymal stem cell exosomes in treating PH.Methods: Exosomes were isolated from control MSC and tadalafil-pretreated MSCs. In vitro and in vivo studies were conducted.Results: MSCTAD-Exo attenuated macrophage inflammation and improved endothelial cell (EC) apoptosis while also reducing pulmonary arterial pressure in a hypoxia-induced rat model. Furthermore, MSC exosomes can mitigate hypoxia-induced proliferation and migration of smooth muscle cells (SMC) by influencing the secretion of endothelial exosomes. MiR-29a-3p has been identified as a crucial mediator in this process, with its expression regulated by cAMP responsive element binding protein 1 (CREB1). MiR-29a-3p exerts anti-inflammatory effects by modulating the expression of ectonucleotide pyrophosphatase/phosphodiesterase 2 (ENPP2). Notably, the anti-inflammatory and anti-vascular remodeling activities of exosomes were diminished following the depletion of MiR-29a-3p.Discussion: MSC treated with tadalafil can secrete better exosomes. MSCTAD-Exo may enhance anti-inflammatory and anti-vascular remodeling properties by upregulating mir-29a-3p expression, providing a novel idea for PH therapy. Future studies could explore the clinical application of this finding. Keywords: exosome, tadalafil, hypoxia pulmonary hypertension, mesenchymal stem cell, miR-29a-3p